2017
DOI: 10.1590/1414-431x20176533
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetylcysteine on spinal cord oxidative stress biomarkers in rats with neuropathic pain

Abstract: N-acetylcysteine (NAC) inhibits nociceptive transmission. This effect has been associated partly with its antioxidant properties. However, the effect of NAC on the levels of lipid hydroperoxides (a pro-oxidant marker), content of ascorbic acid (a key antioxidant molecule of nervous tissue) and total antioxidant capacity (TAC) is unknown. Thus, our study assessed these parameters in the lumbosacral spinal cord of rats with chronic constriction injury (CCI) of the sciatic nerve, one of the most commonly employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…These NAC doses (200–600) are safe, and there is evidence showing that the LD50 of NAC in rats is 1205 mg/kg [ 28 ]. In line with our findings, NAC also imposed antinociceptive effects in the other studies [ 6 – 8 , 29 31 ]; NAC can attenuate neuropathic and inflammatory pain in animal models measuring by hot plate and formalin tests [ 6 , 8 , 29 , 31 ], and chronic apical lesion in humans evaluating by the VAS (visual analog scale) pain score [ 32 ]. Also, single-dose and chronic administration of NAC increases delay time in hot plate test [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…These NAC doses (200–600) are safe, and there is evidence showing that the LD50 of NAC in rats is 1205 mg/kg [ 28 ]. In line with our findings, NAC also imposed antinociceptive effects in the other studies [ 6 – 8 , 29 31 ]; NAC can attenuate neuropathic and inflammatory pain in animal models measuring by hot plate and formalin tests [ 6 , 8 , 29 , 31 ], and chronic apical lesion in humans evaluating by the VAS (visual analog scale) pain score [ 32 ]. Also, single-dose and chronic administration of NAC increases delay time in hot plate test [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…Also, results of Naik et al’s study in the experimentally induced chronic constriction injury (CCI) of sciatic nerve of rats showed that endoneurial oxidative stress plays a critical role in generation of neuropathic pain in CCI model, and NAC can cause significant reduction in mechanical, thermal and cold hyperalgesia in CCI rats, probably through ROS scavenging 55. Similar to these findings, another study in an experimental model of CCI in rats revealed that the pain relieving effect of NAC may be related to its modulation effects on oxidative-stress parameters in the spinal cord 56. There are limited clinical trials about influence of NAC supplementation on treatment of neuropathic pain.…”
Section: Discussionmentioning
confidence: 65%
“…Hyperalgesia remained at all times in CCI rats but returned to pre-injury values through the treatment with NAC [119]. They have also observed that NAC administration is able to protect against the early increase of lipid hydroperoxide levels in the CCI group by the rise of the ascorbic acid amount and the decrease of total antioxidant capacity at later stages [120]. In a recent study, Horst et al have demonstrated the role of the P-p38 protein as a mediator in neuropathic pain and nerve regeneration.…”
Section: Nac In Neuropathic Painmentioning
confidence: 99%